Identity complex : making the case for multiplicity - Hames-Garcia, Michael Roy (University of Minnesota Press, 2011)
In seemingly exhaustive arguments about identity as a category of analysis, we have made a critical error--one that Michael Hames-Garcia sets out to correct in this revisionary look at the making and meaning of social identities. We have asked how separate identities--of race, class, ethnicity, gender, and sexuality--come to intersect. Instead, Hames-Garcia proposes, we should begin by understanding such social identities as mutually constituting one another. Grounded in both theoretical and political practices--in the lived realities of people's experience--"Identity Complex" reinvi